1997
DOI: 10.3928/0098-9134-19971001-07
|View full text |Cite
|
Sign up to set email alerts
|

POST-TRAUMATIC STRESS DISORDER AND THE Elderly Combat Veteran

Abstract: 1 PTSD has been an under-diagnosed syndrome among World War II and Korean era veterans both because of clinical inattention and the way this generation of soldiers coped with traumatic memories throughout their lives. 2 There are psychological, developmental, and situational factors that may cause PTSD symptoms to resurface among older veterans in health care settings. 3 Nurses in health care settings who have frequent contact with the elderly are in a unique position to identify older veterans who might be at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Elderly persons may also experience triggers that younger health professionals may be unfamiliar with and thus likely to overlook, such as participation in the Korean War or interment in relocation camps for Japanese-Americans during World War II. Additionally, elderly persons may exhibit more subtle symptoms of PTSD and may be both more reluctant to discuss these symptoms or to attribute them to psychologic distress [16]. Nonetheless, symptoms of PTSD among some elderly may be particularly long-standing.…”
Section: Epidemiologymentioning
confidence: 92%
“…Elderly persons may also experience triggers that younger health professionals may be unfamiliar with and thus likely to overlook, such as participation in the Korean War or interment in relocation camps for Japanese-Americans during World War II. Additionally, elderly persons may exhibit more subtle symptoms of PTSD and may be both more reluctant to discuss these symptoms or to attribute them to psychologic distress [16]. Nonetheless, symptoms of PTSD among some elderly may be particularly long-standing.…”
Section: Epidemiologymentioning
confidence: 92%
“…In such cases, combat-related PTSD has occurred among some veterans as late as 50 years after combat without previous psychiatric symptoms or re-exposure to battle (Van Dyke et al, 1985;Spiro et al, 1994;Ruskin and Talbott, 1996;Sutker and Allain, 1996). PTSD symptoms may appear when the individual is faced with life events such as retirement, loss of a loved one, diminished sensory capabilities, mobility problems, isolation, cognitive impairment, institutionalization, increased interaction with medical facilities, and ill health (Hermann and Eryavec, 1994;Kaup et al, 1994;Molinari and Williams, 1995;Snell and Padin-Rivera, 1997;Cook, 2001). One study with ex-POWs from WWII and Korea indicated that a relationship exists between higher levels of PTSD and greater numbers of negative health changes, lower social support, and lower death acceptance (Port et al, 2001).…”
Section: Late-onset Ptsdmentioning
confidence: 99%
“…In addition, changes in the physiologic response to stress in older adults may affect both the experience and presentation of anxiety disorders such as PTSD (Kogan et al, 2000). Older veterans may manifest symptoms in more of a somatic rather than a psychological manner and thus be more likely to report physical difficulties instead of emotional ones when compared with younger individuals (Bonwick and Morris, 1996;Clipp and Elder, 1996;Snell and Padin-Rivera, 1997). Older individuals also may not associate their current symptoms with a past trauma and simply determine that symptoms are a result of aging (Falk et al, 1994).…”
Section: Symptom Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, elderly combat veterans today were likely drafted veterans who served in WW2, the Vietnam War, and/or the Korean War. After returning from WW2, "societal demands for conformity and negative stereotypes about mental illness pushed many veterans to hide their post-war trauma confl icts, maintain secrecy, or suppress anxiety and depressive symptoms through a variety of means, not the least of which were psychological mechanisms of repression and denial" [ 60 ]. Speculation may yield the assumption that repression and denial may have been the best defenses suited to survive as it allowed the veteran to function at a level at work and in relationships to sustain them into their elderly age.…”
Section: Ptsd and Disaster Exposure: Lessons Learned From Older Combamentioning
confidence: 99%